Quantitative Approaches to Fiscal Sustainability Analysis : A Case Study of Turkey since the Crisis of 2001 - Budina, Nina; van Wijnbergen, Sweder (World Bank, 2012)
This case study of fiscal sustainability in Turkey after the crisis in 2001 reviews and extends quantitative approaches to fiscal sustainability analysis and brings them together in a user-friendly tool applicable in a data-sparse environment. It combines a dynamic simulations approach with a steady-state consistency approach. It also incorporates user-defined stress tests and stochastic simulations to deal with uncertainty. And it derives the future distribution of debt-output ratios, evaluating the fiscal adjustment required to stabilize them. Value at Risk analysis shows that considerable risks remain unless explicit feedback rules from debt surprises to the primary surplus are implemented.